Tailored nanosized AgInS2-ZnS Heterostructures via Substituted Thioureas: From Growth Dynamics to Optical Performance - Loghina, Liudmila; Houdek, Jakub; Frumarova, Božena; Rodriguez-Pereira, Jhonatan; Slang, Stanislav; Kurka, Michal; Jambor, Roman; Vlcek, Miroslav (Elsevier, 2026)
Tailored nanosized AgInS2-ZnS heterostructures (AISZS) were synthesized via a one-pot, gram-scale protocol using structurally diverse substituted thioureas as organic sulfur sources. This phosphine-free approach enables precise morphological control, yielding rod-like nanocrystals with tunable aspect ratios and enhanced colloidal stability. Systematic variation of thiourea structure revealed a strong correlation with growth kinetics, shape anisotropy, and photoluminescence properties, producing red to near-infrared emission (λPL = 669 - 764 nm), large Stokes shifts (up to 224 nm), and optical bandgaps ranging from 1.77 to 2.18 eV. Among all precursors, 1-octyl-3-phenylthiourea (TU2) delivered highly reproducible heterostructures with narrow size distribution and balanced optical performance. Optimization of the TU2-to-metal ratio further modulated the emission profile and bandgap energy. Comprehensive structural and chemical analysis (STEM, XRD, XPS) confirmed the formation of chalcopyrite-type AgInS2 cores surrounded by amorphous ZnS-rich shells. The optical behavior of AISZS nanocrystals was further investigated in both colloidal dispersion and thin-film formats. Spin-coated films, including those embedded in amphiphilic polymer matrices (PMAO/PS), demonstrated high optical clarity, structural uniformity (AFM), and robust emission. When deposited onto commercial UV LEDs (375 nm), these materials efficiently converted ultraviolet excitation into broadband red emission, confirming their viability for photonic, light-conversion, and optoelectronic applications.
Keywords: nanosized AgInS2-ZnS heterostructures; substituted thioureas; one-pot synthesis; photoluminescence; Stokes shift; thin films; UV-to-red conversion